If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3y + -7) + (-4y + -8) = 0 Reorder the terms: (-7 + 3y) + (-4y + -8) = 0 Remove parenthesis around (-7 + 3y) -7 + 3y + (-4y + -8) = 0 Reorder the terms: -7 + 3y + (-8 + -4y) = 0 Remove parenthesis around (-8 + -4y) -7 + 3y + -8 + -4y = 0 Reorder the terms: -7 + -8 + 3y + -4y = 0 Combine like terms: -7 + -8 = -15 -15 + 3y + -4y = 0 Combine like terms: 3y + -4y = -1y -15 + -1y = 0 Solving -15 + -1y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '15' to each side of the equation. -15 + 15 + -1y = 0 + 15 Combine like terms: -15 + 15 = 0 0 + -1y = 0 + 15 -1y = 0 + 15 Combine like terms: 0 + 15 = 15 -1y = 15 Divide each side by '-1'. y = -15 Simplifying y = -15
| 40.000+1.000x=60.000 | | 1.12x-2/4 | | 1-7/12-3/4 | | 19/.75 | | 5x-2x+2x=-5-8+1 | | 40.000+1.000=60.000 | | 67+x=282 | | -12+4x=6x-32 | | -4(2y+3)=(-18) | | 6/7y=9/14 | | -30=13x-80 | | 3/8k=3/4 | | x+2x+5+4x-7=0 | | 14=-2(x-3)+4 | | 8-7y=-34 | | -1/4x+15=-5 | | 3a+4b+2c=40 | | 9+(-4)x=13 | | -2(y-2)+3(4+3y)=-5 | | 9x^2+6=3x | | -2lx+3l=-60 | | 2xsquared+4x=0 | | 4b+18+3b=74 | | -54-9b-2b=-10 | | 3/i-9 | | 40+x=5.00 | | 6p-2=10(p-2)-4(14-4p)-6 | | x^17=x^15 | | 16=16+4x | | 10x^6-53x^4+36x^2=0 | | Y-26/9=5/6 | | 7x-4=5-8x |